2006
DOI: 10.1111/j.1471-4159.2005.03588.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective deficits in the expression of striatal‐enriched mRNAs in Huntington's disease

Abstract: We have identified and cataloged 54 genes that exhibit predominant expression in the striatum. Our hypothesis is that such mRNA molecules are likely to encode proteins that are preferentially associated with particular physiological processes intrinsic to striatal neurons, and therefore might contribute to the regional specificity of neurodegeneration observed in striatal disorders such as Huntington's disease (HD). Expression of these genes was measured simultaneously in the striatum of HD R6/1 transgenic mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
118
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 122 publications
(131 citation statements)
references
References 87 publications
12
118
1
Order By: Relevance
“…In this study, we further investigated CNS-wide expression of Bcl11b protein and gene expression changes in R6/1 transgenic mice at different stages of disease, as well as in post-mortem caudate samples from human subjects with HD. In addition to showing high levels of expression in the striatum, Bcl11b mRNA is also expressed in other brain regions affected in HD, such as cortex, hippocampus and olfactory bulb from early embryonic stages of development (Leid et al, 2004;Arlotta et al 2005;Desplats et al 2006). Immunohistochemistry experiments on adult mouse brain (>2 months of age) demonstrate that Bcl11b protein expression is also expressed in these regions ( Figure 1).…”
Section: Bcl11b Expression Is Decreased In Hdmentioning
confidence: 96%
See 4 more Smart Citations
“…In this study, we further investigated CNS-wide expression of Bcl11b protein and gene expression changes in R6/1 transgenic mice at different stages of disease, as well as in post-mortem caudate samples from human subjects with HD. In addition to showing high levels of expression in the striatum, Bcl11b mRNA is also expressed in other brain regions affected in HD, such as cortex, hippocampus and olfactory bulb from early embryonic stages of development (Leid et al, 2004;Arlotta et al 2005;Desplats et al 2006). Immunohistochemistry experiments on adult mouse brain (>2 months of age) demonstrate that Bcl11b protein expression is also expressed in these regions ( Figure 1).…”
Section: Bcl11b Expression Is Decreased In Hdmentioning
confidence: 96%
“…Our initial studies showed decreased expression of Bcl11b mRNA in the striata of symptomatic R6/1 transgenic mice (Desplats et al 2006). In this study, we further investigated CNS-wide expression of Bcl11b protein and gene expression changes in R6/1 transgenic mice at different stages of disease, as well as in post-mortem caudate samples from human subjects with HD.…”
Section: Bcl11b Expression Is Decreased In Hdmentioning
confidence: 99%
See 3 more Smart Citations